A comprehensive reproductive health program for vulnerable adolescent girls - Razieh Pourkazemi; Mojgan Janighorban; Zahra Boroumandfar; Firoozeh Mostafavi (BMC, 2020)
Abstract Background Reproductive health of vulnerable adolescent girls is a top priority in global programs. Alcohol consumption, drug abuse, high risk sexual behaviors, sexually transmitted diseases, sexual assault, escape from home, unrestrained sex in the family, history of robbery, imprisonment and living in drug hangouts expose adolescents to different sorts of damage and injury. These adolescent girls are at risk of AIDS and other STDs, unwanted pregnancies, illegal and unsafe abortions, unplanned pregnancy and childbirth, and unsafe motherhood. Therefore, assessing these girls' reproductive health needs and designing programs to improve their sexual and reproductive health seem to be essential. This study will be conducted to design a comprehensive program for improving the reproductive health of vulnerable adolescent girls. Methods The present study is an exploratory sequential mixed methods study (Qual-Quan) designed in three phases. In the first phase, a qualitative study will be used to describe the reproductive health needs of vulnerable adolescent girls, identify facilitating and inhibiting factors, and explain the strategies of reproductive health programs for these girls. Participants will be selected in this phase using purposive sampling method, and the data will be collected through semi-structured interviews. The obtained data will be analyzed using conventional qualitative content analysis. In the second phase, through a quantitative study, the strategies obtained from the qualitative study and review of the literature will be provided to reproductive health care providers, experts, policymakers, and planners to prioritize and select the best strategies. In the third phase, the initial draft of the program will be formulated based on prioritized strategies and will be proposed in a panel comprised of specialists in the areas of reproductive and sexual health, health promotion, social injuries and a psychiatrist. Finally, the final program will be developed and presented after obtaining the agreement and approval of the panel members. Discussion Designing a program based on a qualitative study, review of the existing evidence and programs, and using the opinions of experts in different areas can lead to different aspects of reproductive and sexual health of vulnerable adolescent girls. On the other hand, taking into account all cultural sensitivities and taboos as well as political, economic and social barriers, the development of such a program can provide the appropriate possibility of presenting comprehensive reproductive and sexual health services to vulnerable adolescent girls and achieve the goals agreed universally.